Open factory events as triggers of interactive learning in organizations - Brunetti, Federico; Bonfanti, Angelo; Castellani, Paola; Giaretta, Elena (Development and learning in organizations, 2018)
Purpose The purpose of this paper is to present and discuss an unconventional approach for developing organizational learning inside companies. The subject of this paper is the interactive mode of organizational learning – involving shared understanding and sense-making – which has proven useful in the current turbulent era and complex competitive environment. Design/methodology/approach The paper is based on an inductive and phenomenon-driven approach. The data collection method consists of interviews with involves informants. The empirical context of the research is Open Factory – the largest open-door event for industrial manufacturing in Italy. Findings Companies participating in Open Factory gained several benefits in terms of interactive learning. In particular, intra-organizational knowledge sharing, staff motivation, and more focused organizational identity were reported as the most relevant advantages. Practical implications Companies eager to enhance their interactive mode of organizational learning should seriously consider taking part in events such as Open Factory or should strive to create a similar event. Originality/value To the best of the authors’ knowledge, this paper is the first to describe and analyze open-door events for manufacturing companies as a source of organizational learning.